Protease Activity of Campylobacter jejuni HtrA Modulates Distinct Intestinal and Systemic Immune Responses in Infected Secondary Abiotic IL-10 Deficient Mice - Schmidt, Anna-Maria (Front Cell Infect Microbiol, 2019)
Even though human Campylobacter jejuni infections are progressively increasing worldwide, the underlying molecular mechanisms of pathogen-host-interactions are still not fully understood. We have recently shown that the secreted serine protease HtrA plays a key role in C. jejuni cellular invasion and transepithelial migration in vitro, and is involved in the onset of intestinal pathology in murine infection models in vivo. In the present study, we investigated whether the protease activity of HtrA had an impact in C. jejuni induced acute enterocolitis. For this purpose, we perorally infected secondary abiotic IL-10(−/−) mice with wildtype C. jejuni strain NCTC11168 (11168(WT)) or isogenic bacteria carrying protease-inactive HtrA with a single point mutation at S197A in the active center (11168(HtrA−S197A)). Irrespective of the applied pathogenic strain, mice harbored similar C. jejuni loads in their feces and exhibited comparably severe macroscopic signs of acute enterocolitis at day 6 postinfection (p.i.). Interestingly, the 11168(HtrA−S197A) infected mice displayed less pronounced colonic apoptosis and immune cell responses, but enhanced epithelial proliferation as compared to the 11168(WT) strain infected controls. Furthermore, less distinct microscopic sequelae in 11168(HtrA−S197A) as compared to parental strain infected mice were accompanied by less distinct colonic secretion of pro-inflammatory cytokines such as MCP-1, IL-6, TNF, and IFN-γ in the former as compared to the latter. Strikingly, the S197A point mutation was additionally associated with less pronounced systemic pro-inflammatory immune responses as assessed in serum samples. In conclusion, HtrA is a remarkable novel virulence determinant of C. jejuni, whose protease activity is not required for intestinal colonization and establishment of disease, but aggravates campylobacteriosis by triggering apoptosis and pro-inflammatory immune responses.